Public Accountants' Perceptions of Indonesia’s Readiness for Accounting Digitalization in Industry 5.0 - Eka Astrit Pitaratu; Halsya Handayani; Aldy Laana Larongga; Fitriani (IECON: International Economics and Business Conference, 2025)
This study explores the perceptions of public accountants regarding Indonesia’s readiness to adopt accounting digitalization in the era of Industry 5.0. As technological integration accelerates across sectors, the accounting profession faces urgent demands to adapt to artificial intelligence (AI), big data, and automation. This research aims to assess how well-prepared Indonesia is from the perspective of accounting professionals, who are directly impacted by these shifts. Using a quantitative research approach, data were collected through structured questionnaires distributed to certified public accountants across major cities in Indonesia. The study employed descriptive and inferential statistical methods to analyze the responses and identify patterns of perception. The findings reveal a generally positive perception of Indonesia’s digital transformation, with particular confidence in technological infrastructure and institutional support. However, concerns persist regarding the readiness of human resources and regulatory alignment. The results also suggest regional disparities in readiness levels, pointing to a need for more targeted policy intervention and continuous professional development. This study contributes to the literature by highlighting the voice of practitioners in the national discourse on digital transformation in accounting. It underscores the importance of collaboration among government, academia, and industry stakeholders to ensure a cohesive and sustainable digital ecosystem. The implications of this research are particularly relevant for policymakers, regulators, and educational institutions aiming to align Indonesia’s accounting profession with the demands of Industry 5.0.